Case report: From monkeypox pharyngitis to myopericarditis and atypical skin lesions - Sanromán Guerrero, María Ascensión; Sánchez, Elena Hernández; Ruanes, Belén de Nicolás; Fernández-González, Pablo; Ugalde, Sonia Antoñana; Leal, Alejandra González; Fernández, Marcelo Sanmartín; Rodríguez, Jose Javier Alarcón; Martinez Garcia, Laura; Escudero, Rosa; Méndez, Maria Ángeles Fernández; Zamorano Gómez, Jose Luis; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background A global outbreak of the human monkeypox virus (HMPXV), first identified in May 2022, was declared a health emergency of international concern on 23 July 2022. Before the global outbreak, monkeypox cases were mostly confined to central and west African countries, where this virus is prevalent. Close contact, mainly sexual contact, is supposed to be the main route of transmission, and it is remarkable that the incidence is higher in men who have sexual relationships with other men. Case summary A 40-year-old Caucasian man arrived at the emergency department complaining of oppressive epigastric pain extending to the chest after a diagnosis of pharyngitis, which was suspected to be caused by the human monkeypox virus. Based on the clinical symptoms, physical examination, serum cardiac biomarkers, and electrocardiographic findings, he was diagnosed with myopericarditis. The real-time PCR for human monkeypox in skin lesions, urine, plasma, and the oropharyngeal swab was positive. The peak of troponin I was 20.6 ng/ml, and the electrocardiogram showed an upward concavity in the ST segment in diffuse leads, which was in agreement with the previous diagnosis. The presence of edema, subepicardial, and myocardial late gadolinium enhancement, and increased values on T1 mapping in the cardiac MRI were in agreement with the diagnosis of myopericarditis. Antiviral treatment with tecovirimat was started with excellent tolerability. After 6 days, the patient recovered and was discharged. Discussion To our knowledge, this is one of the first reported cases of myopericarditis due to human monkeypox infection, which was confirmed by a cardiac MRI following modified Lake Louise criteria. The short span between the onset of the mucocutaneous symptoms and the myocardial damage suggests a pathogenic association. Furthermore, the active viral replication in plasma samples and the negative results on real-time PCR for other viruses support this clinical association.